Predictors of outcome in palliative colonic stent placement for malignant obstruction. Issue 2 (2nd December 2013) - Abbott, S; Eglinton, T W; Ma, Y; Stevenson, C; Robertson, G M; Frizelle, F A
Abstract: Background: Emergency surgery for large bowel obstruction carries significant morbidity and mortality. After initially promising results, concerns have been raised over complication rates for self-expandable metal stents (SEMS) in both the palliative and bridge-to-surgery settings. This article documents the technique used at the authors' institution, and reports on success and complication rates, as well as identifying predictors of endoscopic reintervention or surgical treatment. Methods: Data were collected for a prospective cohort of consecutive patients undergoing attempted colonoscopic SEMS insertion at a single institution between 1998 and 2013. Multivariable logistic models were fitted to assess possible predictors of endoscopic reintervention and surgical treatment. Results: Palliative SEMS insertion was attempted in 146 patients. Primary colorectal cancer was the most common cause of obstruction (95·2 per cent). The majority of patients (77·4 per cent) were treated in an acute setting, with a high technical success rate of 97·3 per cent. The perforation rate was 4·8 per cent and the 30-day procedural mortality rate 2·7 per cent. No predictors of early complications were identified, although patients with metastases and those who received chemotherapy were more likely to have late complications. Some 30·8 per cent of patients required at least one further intervention, with 11·0 per cent of the cohort requiring a stoma. Endoscopic reintervention was largely successful. Conclusion: SEMS offer a valid alternative to operative intervention in the palliative management of malignant large bowel obstruction. Patients receiving chemotherapy are more likely to receive endoscopic reintervention, which is largely successful. Abstract : Successful in the majority